A Case Study On Nestle : The World's Dominant Food And Beverage Company - Facing Up To The Challenges In The 21st Century - Mohd Nasir, Nik Naharudin (2005)
Since its establishment in 1866 by Swiss-German pharmacist Henri Nestle, Nestle had grown largely by mergers and acquisitions into the world's leading food and beverage company. Based on the identified strengths, weaknesses, opportunities and treats, a set of strategies was formulated and compared against possible alternative strategies. These were then followed by possible methodologies for the implementation, evaluation and control of the proposed strategies.